IDENTIFIKASI SISTEM KERJASAMA PETANI PENGGARAP DAN PEMILIK TANAH DALAM KAITANNYA DENGAN PEMERATAAN PENDAPATAN PETANI PADI SAWAH BERIRIGASI (Suatu Studi Terhadap Kelembagaan Petani pada Wilayah Jaringan Sekunder Irigasi Dayah Daboh & Lamcot Kab Aceh Besar) - Edy Marsudi (Jurnal Agrisep, 2011)
The Identification of Cooperation System between Farmer and Land Owner In Creating an Even Income Distribution of Irrigated Rice Field Farmers(A Study toward the Institutional of Farmers in Secondary Network of Irrigation inDayah Daboh and Lamcot in District of Aceh Besar)ABSTRACT.The negotiation between farmer and land owner has resulted in three kinds of farmer cooperation forms, known as Type I Mawah System, Type II Mawah System, and Contractual System. The aim of this research is to find out the type of cooperation which is able to create a fair and better income distribution not only for the farmer but also for the land owner. This research used a survey method. The stratified random sampling technique was used to pick up the sample from population distributed in rice field spread out area. Five gampong (villages) were chosen from each spread out area. Meanwhile, two farmers and two land owners who do not work the land are chosen from each gampong. The result shows that the Type II Mawah System is more able to provide a bigger income proportion and create a fair and better income distribution for both the farmer and the land owner than the other two systems. It is really recommended that the farmer and the land owner choose the Type II Mawah System as the cooperation system and always base the deal on it.